2022
DOI: 10.3233/shti220200
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Application and Assessment During the COVID-19 Pandemic

Abstract: Telemedicine had a significant increase during the novel coronavirus (COVID-19) pandemic, which is still on course. In different parts of the world, healthcare units had to adapt their practice, and several assistance services were remotely delivered. The present study is a systematic review of studies that had applied telemedicine during the COVID-19 pandemic and had assessed its effects on the delivered care. We have covered a 1-year period in order to assess the initiatives developed during the pandemic tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Telehealth was investigated and reported in 12 of the included reviews ( Dhada et al, 2021 ; Hojaij et al, 2020 ; Murphy et al, 2022 ; Alom et al, 2021 ; Lu et al, 2021 ; Mostafaei et al, 2022 ; Salehi et al, 2022 ; Zapała et al, 2022 ; Di Cosimo et al, 2022 ; Lignou et al, 2022 ; Pascual et al, 2022 ; Bezerra et al, 2022 ); a summary of main findings is provided in Supplementary file 1h . Salehi et al, 2022 reported that telemedicine use in breast cancer patients was the most common investigated in studies exploring cancer-specific use of telemedicine.…”
Section: Resultsmentioning
confidence: 99%
“…Telehealth was investigated and reported in 12 of the included reviews ( Dhada et al, 2021 ; Hojaij et al, 2020 ; Murphy et al, 2022 ; Alom et al, 2021 ; Lu et al, 2021 ; Mostafaei et al, 2022 ; Salehi et al, 2022 ; Zapała et al, 2022 ; Di Cosimo et al, 2022 ; Lignou et al, 2022 ; Pascual et al, 2022 ; Bezerra et al, 2022 ); a summary of main findings is provided in Supplementary file 1h . Salehi et al, 2022 reported that telemedicine use in breast cancer patients was the most common investigated in studies exploring cancer-specific use of telemedicine.…”
Section: Resultsmentioning
confidence: 99%
“… 22 This process had positive effects on the treatment of different conditions, including chronic diseases, mental disorders, and oncologic diseases. 23 Telemedicine was also applied to the field of neuropsychological assessment. 24 Regarding the rehabilitation of sABI few experiences of telemedicine approach have been described.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, reliance on telehealth exponentially increased, and for some chronic conditions, it not only facilitated care delivery but also improved health outcomes [ 26 , 27 ]. In our study, although mHealth may have supported adherence, this effect was moderated by the duration of the lockdown, which negatively impacted app use over time and consequently affected hydroxyurea adherence.…”
Section: Discussionmentioning
confidence: 99%